2022
DOI: 10.1021/acs.jproteome.2c00196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fucose-Specific Lectins to Improve Quantitative AFP-L3 Assay for Diagnosing Hepatocellular Carcinoma Using Mass Spectrometry

Abstract: Glycoproteins have many important biological functions. In particular, aberrant glycosylation has been observed in various cancers, such as liver cancer. A well-known glycoprotein biomarker is α-fetoprotein (AFP), a surveillance biomarker for hepatocellular carcinoma (HCC) that contains a glycosylation site at asparagine 251. The low diagnostic sensitivity of AFP led researchers to focus on AFP-L3, which has the same sequence as conventional AFP but contains a fucosylated glycan. AFP-L3 has high affinity for L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…We used a combination or one of AAL, LCA, UEA-I lectins, which can bind a1,6, a1,2, and a1,3 linked fucoses. 32,53 Thus, this method can quantify glycoprotein with stages with hyperfucosylation of lung metastatic saliva (Fig. 6C).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We used a combination or one of AAL, LCA, UEA-I lectins, which can bind a1,6, a1,2, and a1,3 linked fucoses. 32,53 Thus, this method can quantify glycoprotein with stages with hyperfucosylation of lung metastatic saliva (Fig. 6C).…”
Section: Discussionmentioning
confidence: 96%
“…We used a combination or one of AAL, LCA, UEA-I lectins, which can bind α1,6, α1,2, and α1,3 linked fucoses. 32,53 Thus, this method can quantify glycoprotein with core or antenna fucoses. IgG is one of the most abundant fucosylated glycoproteins in serum, and its abundance correlates with humoral immune status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several liquid chromatography with tandem mass spectrometry (LC–MS/MS) methods have been developed to profile and identify different glycoforms of AFP, which are based on quantification of AFP-specific glycopeptides through digestion of proteins enriched from plasma or serum samples. ,, These methods utilize glycopeptides representing the AFP glycoforms without core fucosylation (AFP-L1) and with core fucosylation (AFP-L3) to calculate the relative abundance of AFP-L3 glycoforms (AFP-L3%). Other studies also utilized enzymes and chemical treatment to release glycans from AFP and identified the glycan structure by electrospray ionization (ESI) and matrix-assisted laser desorption/ionization (MALDI) coupled with MS. ,, During MS analysis, glycans and glycopeptides require different collision energies for structure and sequence identification based on fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Glycosylation of LAMP2 and SV40 serves as a protective mechanism against HCC (Pousset et al, 1997;Chiu et al, 2022). Glycosylation of HCC mostly occurs in oncogenes such as AFP, AACT, and MDR, which can be used as risk factors for HCC (Ledoux et al, 2003;Lee et al, 2022). Glycosylation of these genes is not only involved in the molecular mechanism of HCC progression but is also closely related to tumor drug resistance.…”
Section: Introductionmentioning
confidence: 99%